QUALITY BY DESIGN (QBD) APPROACH FOR OPTIMIZATION OF MANGIFERIN-LOADED NANOPARTICLES FOR THE SAFE AND EFFECTIVE TREATMENT OF BREAST CANCER - K. V., SHIJITH; CHARYULU, R. NARAYANA; CHANDRAN, SARATH; PATIL, PRAKASH; JOSE, JOBIN (International Journal of Applied Pharmaceutics, 2025)
Objective: The primary objective of this investigation was to develop mangiferin (MGF)-loaded bovine serum albumin (BSA) nanoparticles using a Quality by Design (QbD) approach. The study involved characterizing the optimized nanoparticles to confirm their successful formation, assessing their ability to inhibit the growth of MCF-7 breast cancer cell lines, and conducting a toxicity assay following OECD protocol 423. Methods: MGF-loaded BSA NP was prepared by the modified desolvation method with necessary modification. For the optimization, a QbD framework with a Central Composite Design (CCD) was employed. The optimization was done by evaluating the effect of critical factors such as BSA concentration, MGF loading, and stirring speed on selected responses such as particle size (Ps), polydispersibility index (PDI), zeta potential(Zp) and encapsulation efficiency (EE). The optimized formulation was further analyzed using SEM, FT-IR, and XRD and assessed for in vitro drug release, as well as using the MTT assay, it demonstrated anticancer efficacy against MCF-7 breast cancer cells. Finally, the safety profile of the formulation was established by acute toxicity study in Albino Wistar Rat as per OECD protocol 423. Results: Successful incorporation of MGF into BSA NP was achieved by modified desolvation technique. 20 formulations were developed as per CCD. The optimized nanoparticles exhibited a Ps of 96.83 nm, PDI of 0.25, Zp of-22.9 mV, and EE of 70.37%. SEM confirmed the spherical morphology, and FT-IR/XRD verified that there are no chemical reactions. The in vitro release study showed 90% drug release within 8 h. In vitro anticancer assays revealed dose-dependent efficacy (ID50:22.32 µg/ml) and comparable with that of doxorubicin. The statistical significance was observed between the optimized formulation and control groups. Acute toxicity studies confirmed its safety (no mortality/toxicity at 2000 mg/kg). Conclusion: The current investigation shows that MGF-loaded BSANP have a promising release profile for achieving better anti-breast cancer activity.